PERANAN DEKOMPOSER NABATI TERHADAP PERTUMBUHAN POPULASI SEL ALGA - Junus, Mochammad; Widodo, Agung Sugeng; Suprapto, Wahyono; Zamrudy, Windi (Metamorfosa: Journal of Biological Sciences, 2016)
Indonesia has programmed units of biogas as an energy producer. By-products such as organic sludge. Liquid separation of organic sludge biogas unit will be the terrestrial and aquatic plant fertilizer. Water plant that uses a liquid organic sludge biogas unit (LOSBGU) using vegetable decomposer were expected to be a very good influence on the increase of alga cells. The results showed that the addition of vegetable LOSBGU and decomposers in the media for 12 days alga could produce alga cells very significantly, however, its interaction was not significant. It was concluded that the addition of vegetable LOSBGU and decomposers in alga was very good media to enhance cell growth and its multiplication was also quite high. As suggestion, the use of  LOSBGU is needed to increase the production of alga.
Keywords: manure, LOSBGU, fertilizer, feed, food, energy